(untitled) (Fiep Bulletin - online, 2023)
Introduction: The postpartum period can be marked by several complications, including sexual dysfunction, requiring multidisciplinary health intervention Objective: To point the main physiotherapeutic approaches in the rehabilitation of sexual dysfunctions in puerperal women. Methodology: This article is an integrative literature review through the databases of the virtual libraries Pubmed, PEDro Platform and Scielo; using the descriptors, through the following search schemes: Physiotherapy, AND Sexual Dysfunction Physiological OR Pelvic Floor Disorders OR Pelvic Pain AND Postpartum Period, and their equivalents in Portuguese, in the period from 2010 to 2022. Results: Initially, 403 articles were found with parameters established by the search strategy, with 41 articles eligible for reading in full and in the evaluation of the eligibility criteria, 5 articles were included for this review. Conclusion: Physical therapy, through training the pelvic floor muscles, use of verbal commands, cryotherapy, biofeedback and electrical stimulation, has an impact on the sexual function of women in the puerperal period, with regard mainly to the weakness of the pelvic floor muscles and pain in sexual intercourse.